Experimental study on sedimentation characteristics of fine tailings. (August 2019) - Li, Quanming; Liu, Yinkun; Zhang, Hong
Abstract: The experimental results of sedimentation characteristics of fine-grained tailing at home and abroad are summarized. For fine-grained tailing dam, the particle size of tailing, the discharge concentration of tailing and pore water pressure has significant effects on the sedimentation characteristics of fine-grained tailing dam. Different particle size of tailing will lead to a different structure of tailing deposition, which directly affects the sedimentation characteristics and stability of tailing. The increase of discharge concentration and pore water pressure will also lead to adverse results of tailing sedimentation characteristics.